2017
DOI: 10.2147/dddt.s107195
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of antimicrobial peptide DP7 combined with antibiotics against multidrug-resistant bacteria

Abstract: Antibiotic-resistant bacteria present a great threat to public health. In this study, the synergistic effects of antimicrobial peptides (AMPs) and antibiotics on several multidrug-resistant bacterial strains were studied, and their synergistic effects on azithromycin (AZT)-resistance genes were analyzed to determine the relationships between antimicrobial resistance and these synergistic effects. A checkerboard method was used to evaluate the synergistic effects of AMPs (DP7 and CLS001) and several antibiotics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(80 citation statements)
references
References 28 publications
3
67
0
Order By: Relevance
“…To resolve the problem of antimicrobial resistance, multiple AMPs have been developed in recent years as alternative antibiotics (16)(17)(18)(19), and a number of AMPs exhibited high antimicrobial efficacy and broad-spectrum activity (17,20). The present study suggested that L12 was effective in susceptibility tests against gram-positive bacteria, particularly S. aureus.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…To resolve the problem of antimicrobial resistance, multiple AMPs have been developed in recent years as alternative antibiotics (16)(17)(18)(19), and a number of AMPs exhibited high antimicrobial efficacy and broad-spectrum activity (17,20). The present study suggested that L12 was effective in susceptibility tests against gram-positive bacteria, particularly S. aureus.…”
Section: Discussionmentioning
confidence: 69%
“…The additional antibacterial molecules tested presented additive effects. A previous study demonstrated that antibacterial drugs with similar molecular mechanisms or that target the same molecular components, exert improved synergistic effects compared with combinations of drugs with dissimilar function (17). Additionally, vancomycin and ceftazidime inhibit the cell wall synthesis of gram-positive bacteria by multiple mechanisms (29), which is hypothesized to be responsible for their synergistic effects with L12.…”
Section: Discussionmentioning
confidence: 99%
“…According to our data intercommunication was also between the terms of setting of antibacterial therapy and level of vitamin D (r = 0.57, P < 0.05), lactoferrin (r = 0.40, P < 0.05) and hBPI (r = 0.38, P < 0.05) in the blood serum. The obtained data look logical, if to take into account circumstance that antimicrobial peptides together with antibacterial preparations can show a synergistic effect in regard to pathogenic causative agents and promote effictive etiotropic therapy [27,28].…”
Section: Resultsmentioning
confidence: 97%
“…Multidrug resistant (MDR) bacterial infections are a growing and significant threat to public health, and are caused by species including methicillin resistant S. aureus, vancomycin resistant E. faecalis, and the globally disseminated CTX-M type ESBL-expressing strains of E. coli (30, 31). Antimicrobial peptides (AMPs) are of interest as alternatives to traditional antibiotics because of their broad spectrum antimicrobial properties and efficacy against MDR bacteria; however, to date they have met limited success due to their often non-selective toxicity (3236). We previously reported that chitosan based cationic polymers showed antimicrobial activity against a variety of MDR pathogens (12, 2022).…”
Section: Discussionmentioning
confidence: 99%